Karakterisasi Sensor Cahaya Light Dependent Resistor (LDR) - Annas, Muhamad Azwar; Widodo, Aris; Aisiyah, Muktamar Cholifah; Ningrum, Izza Eka; Makrufah, Dini (MASALIQ, 2022)
Research on the Characterization of the Light Dependent Resistor (LDR) Light Sensor has been carried out with the aim of understanding the characteristics of the LDR light sensor, for processing changes in the LDR resistance value as a measurement of light intensity and for accessing an 8-bit resolution ADC by entering the LDR light sensor voltage result. The value of the resistance on the LDR depends on the size of the light received by the LDR itself. In addition, the greater the intensity of light hitting the LDR surface, the smaller the resistivity. On the other hand, the smaller the intensity of light hitting the LDR, the greater the resistance value. The basic principle used in the use of LDR resistors as components of this sensor is the change in the resistance value and the amount of current flowing in the circuit. In this experiment, the distance variations of 0cm, 3cm, 6cm, 9cm, 12cm, 15cm, 18cm, 21cm, 24cm, 27cm and 30cm were used. LDR characteristics are slow response in identifying light intensity, the greater the light intensity the smaller the resistivity, LDR can be used to read changes in light intensity and data retrieval can be done with an op-amp and a microcontroller.